A comprehensive review on telecommunication challenges of microgrids secondary control. (September 2022) - Sheykhi, Negar; Salami, Abolfazl; Guerrero, Josep M; Agundis-Tinajero, Gibran D; Faghihi, Tayebe
Highlights: A comprehensive review of secondary level control structures has been studied. Communication network subjects and control methods of microgrids are explained and discussed. Major challenges of communication network on microgrid control have been analysed. Time delay has been highlighted as an effective communication disturbance. Abstract: The development of distributed energy resources in distribution networks has created a new concept called microgrids. Their control is one of the main development issues that must be addressed before any implementation process. In this paper, a comprehensive literature review of the main hierarchical control algorithms such as centralized, decentralized, and distributed, with a focus on the secondary level, with an emphasis on their main strengths and weaknesses are discussed and compared. Microgrid communication infrastructures allow the use of different control schemes for the secondary control layer which is given the importance of secondary control over the stable and reliable performance of microgrids, and the lack of comprehensive reference for researchers. Also, provides a literature review on current key issues regarding microgrid secondary control strategies with respect to communication network challenges. The issue of secondary control is discussed with a focus on challenges such as time delays. Also Distributed control methods at the secondary level to reduce the use of the communication network and subsequently reduce communication network delays are discussed.